Dirichlet's theorem related prime gap statistics - Pah, Chin Hee (Universiti Putra Malaysia, 2016)
In this paper, we investigate a special prime gap problem which results from Dirichlet's theorem and relate it to the twin prime conjecture. Then we numerically study the density of several classes of the prime gap that not exceeding a natural number N. A few open problems are given.